How Effective Are School Professionals at Identifying Students Who Might Benefit From Cognitive Behavioral Therapy? Baseline Data From the Adaptive School-Based Implementation of Cognitive Behavioral Therapy Trial - Choi, Seo Youn; Rusch, Amy; Koschmann, Elizabeth; Bilek, Emily L.; Lane, Annalise; Abelson, James L.; Eisenberg, Daniel; Himle, Joseph A.; Fitzgerald, Kate D.; Liebrecht, Celeste; Kilbourne, Amy M.; Smith, Shawna N. (Frontiers in Education, 2022)
School professionals (SPs) are increasingly tasked with providing mental health treatment for students. Successful implementation of school-based mental health evidence-based practices (EBPs) can reduce students’ depression and anxiety, but requires identification of appropriate students to benefit from these interventions. We examined the ability of SPs to identify students appropriate for cognitive behavioral therapy (CBT), using baseline data collected for a large-scale implementation trial. 169 SPs from 94 Michigan high schools were asked to identify up to 10 students whom they believed could benefit from CBT. Identified students were asked to complete a baseline survey. We examined the proportion of consented students who screened positive for depression or anxiety, based on the Patient Health Questionnaire modified for teens and the Generalized Anxiety Disorder questionnaire, overall and by key school- and SP-level factors. Of the 1,347 students identified by 149 SPs, 899 students completed the survey. Of those students, 87% exhibited any depression or anxiety symptoms (score of five or higher) and 66% showed moderate/severe symptoms (score of ten or higher). Per SP, the proportion of consented students who screened positive for any depression or anxiety symptoms was on average 0.88. The effectiveness of SPs’ student identification did not vary significantly by school-specific role, prior CBT training, or geography. Results suggest that SPs can effectively identify students appropriate for CBT given minimal training and resources; an important first step in increasing student access to school-based mental health care.